VD_FINDINFO Arrêt / 2012 / 947 vom 27. Dezember 2012 - VD Tribunal cantonal (2012)
EXPERTISE PSYCHIATRIQUE, ADMISSION DE LA DEMANDE, ENQUÊTEEN GÉNÉRAL, TUTELLE | 369 CC, 374 al. 2 CC, 380 CPC, 489 CPC, 75 al. 2 LTF, 75 LTF, 93 LTF